Metacognitive Strategy and Its Interplay Towards Speaking Performance: A Case in SMPN 29 Buton - Vivy Luviana; Wa Ode Venny Novahriana Jimad; La Ode Achmad Suherman (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2022)
Metacognitive strategies are important strategies in many areas of learning. The aims of this study were to find out the influence of metacognitive strategy in students of SMPN 29 BUTON’ speaking performance, that is, to know the extent of correlation between metacognitive strategies and speaking performance and to know the types of metacognitive strategies used in speaking. The method of this study was a mixed method design, combining quantitative and qualitative approaches. The types of metacognitive strategies used in speaking were first analyzed, which was followed by quantifying the correlation level between metacognitive strategies in speaking and the speaking performance. The instruments used in this study were speaking test and metacognitive strategy questionnaire. The population of this study was students of SMPN 29 BUTON in the academic year of 2020/2021. The results of this study indicated that the level of metacognitive strategy use in speaking performance of students of SMPN 29 BUTON and the level of their speaking performance are moderate (M = 2.03 and M = 63) as well as the correlation between metacognitive strategy and their speaking performance (R = 0.45 and probability value = 0.00). Furthermore, it was found the frequency of using several types of metacognitive strategies in planning and monitoring speaking was quite high, but not in metacognitive strategies for evaluation.